1999
DOI: 10.1016/s0928-8244(99)00087-5
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of immunisation against diphtheria, pertussis and tetanus (DPT) in relation to sudden infant death syndrome

Abstract: Epidemiological evidence indicates infants immunised against diphtheria, pertussis and tetanus (DPT) are at decreased risk of sudden infant death syndrome (SIDS). Asymptomatic whooping cough and pyrogenic toxins of Staphylococcus aureus have been implicated in the aetiology of SIDS. The objectives of the present study were: (1) to determine if the DPT vaccine induced antibodies cross-reactive with the staphylococcal toxins; (2) to determine if antibodies to the pertussis toxin (PT) and the staphylococcal toxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…[30][31][32] Although this may indicate that immunization against pertussis protects children from death attributable to unrecognized B pertussis infection, a recent study suggested that immunization with diphtheria-tetanus-pertussis vaccine also induces antibodies that cross-react with pyrogenic staphylococcal toxins, which have been implicated in several cases of SIDS. 33 As an initial surprise to us, the rates of positive PCR findings were similar for case subjects and control subjects and the rate was actually higher for control subjects (5.3%) than case subjects (1.7%) when NPS results were compared. A significant decrease in positivity rates from the first year to the second year of the study (6.7% vs 2.9%) was observed (data not shown).…”
Section: Discussionmentioning
confidence: 76%
“…[30][31][32] Although this may indicate that immunization against pertussis protects children from death attributable to unrecognized B pertussis infection, a recent study suggested that immunization with diphtheria-tetanus-pertussis vaccine also induces antibodies that cross-react with pyrogenic staphylococcal toxins, which have been implicated in several cases of SIDS. 33 As an initial surprise to us, the rates of positive PCR findings were similar for case subjects and control subjects and the rate was actually higher for control subjects (5.3%) than case subjects (1.7%) when NPS results were compared. A significant decrease in positivity rates from the first year to the second year of the study (6.7% vs 2.9%) was observed (data not shown).…”
Section: Discussionmentioning
confidence: 76%
“…B. pertussis infection may have indirect effects such as the impairment of the immune system and an increased likelihood of co-infections [ 31 , 34 ]. DTP immunisation may also induce cross-reactivity to other agents and their products [ 35 ]. These findings may indicate either a lack of sensitivity in diagnostic testing or a protective effect of the immunisation, independent of direct prevention of B. pertussis infection.…”
Section: Discussionmentioning
confidence: 99%
“…As for older SIDS cases, DTPP±Hib vaccination does not constitute a risk factor for early SIDS, even in infants vaccinated before 3 months of age. Moreover, recent epidemiological evidence indicates that infants immunized against DTP are perhaps at decreased risk of SIDS (25, 26).…”
Section: Discussionmentioning
confidence: 99%